The effect of entrepreneurial work environment on the organizational citizenship behavior - ranay, frelyn; Abun, Damianus; P. Julian, Fredolin; Quinto, Egdona A. (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2023)
Abstract: The study aimed to examine the effect of entrepreneurial work environment on organizational citizenship behaviour. To deepen the concept of the study, literature that is related to the current topic was reviewed. The study applied the assessment and correlational research design. The population of the study was all the employees of the Divine Word College of Laoag and total enumeration sampling was used. To gather the data, adopted research questionnaires were used and weighted mean and analysis of variance were used to analyze the data. The study found that the entrepreneurial work environment and organizational citizenship behaviour of the employees are considered high and the analysis of variance suggests that there is a significant correlation between entrepreneurial work environment and organizational citizenship behaviour. This suggests that positive changes in the entrepreneurial work environment are necessary for enhancing organizational citizenship behaviour.